2006
DOI: 10.1123/mcj.10.3.244
|View full text |Cite
|
Sign up to set email alerts
|

A Kinematic Analysis of How Young Adults with and Without Autism Plan and Control Goal-Directed Movements

Abstract: We examined the planning and control of goal-directed aiming movements in young adults with autism. Participants performed rapid manual aiming movements to one of two targets. We manipulated the difficulty of the planning and control process by varying both target size and amplitude of the movements. Consistent with previous research, participants with autism took longer to prepare and execute movements, particularly when the index of difficulty was high. Although there were no group differences for accuracy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
138
3
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 131 publications
(165 citation statements)
references
References 23 publications
22
138
3
2
Order By: Relevance
“…Across the literature movement planning is often cited to be affected whereas movement execution is found to be unaffected (e.g., Mari et al 2003;Rinehart et al 2001). There are, however, a number of instances where individuals with autism demonstrate slowed movement execution (Glazebrook et al 2006(Glazebrook et al , 2008Rinehart et al 2006b;Szatmari et al 1990). Future research should strive to identify the root of these differences across protocols.…”
Section: Discussionmentioning
confidence: 97%
“…Across the literature movement planning is often cited to be affected whereas movement execution is found to be unaffected (e.g., Mari et al 2003;Rinehart et al 2001). There are, however, a number of instances where individuals with autism demonstrate slowed movement execution (Glazebrook et al 2006(Glazebrook et al , 2008Rinehart et al 2006b;Szatmari et al 1990). Future research should strive to identify the root of these differences across protocols.…”
Section: Discussionmentioning
confidence: 97%
“…parameters referring to joint motions and angles at specific points in a movement and typically reported in terms of the velocity, acceleration (change in velocity) and jerk (change in acceleration) of a particular point on the body. Such studies have revealed differences between autistic and typical individuals [39][40][41][42][43][44][45].…”
Section: (D) Upper Limb Movementsmentioning
confidence: 99%
“…To illustrate, Glazebrook et al [41,42] found that adults with autism required more time both during movement initiation and execution for manual aiming movements, while Rinehart and colleagues have reported that autistic children [40] and young adults [46] require more time to prepare point-to-point movements (moving from one point in space to another). Further work uses the reach-to-grasp task where, upon presentation of a cue, participants move their hand from a start position to grasp a target object.…”
Section: (D) Upper Limb Movementsmentioning
confidence: 99%
“…Children with ASD find more difficulty planning their actions during drawing tasks [6] and are less likely to express end-state comfort tendencies (i.e., the idea that an individual will begin an action in an uncomfortable position if that allows them to end the task in a more comfortable/ functional position) than neurotypical children [9]. Children with ASD also express slower reaction times (RT) and movement times (MT) during reaching movements when compared to neurotypical children [11][12][13].…”
Section: Motor Planning Deficitsmentioning
confidence: 99%